2022
DOI: 10.3389/fpubh.2022.953593
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Otago exercise programme on the prevention of falls in older adult: A systematic review

Abstract: ObjectiveTo improve the quality of life of older adult in their later years, by increasing the physical activity participation of older adult, the occurrence of falls accident scores in older adult can be prevented. This paper comprehensively summarizes the origin, development, participation forms, and fitness effects of the Otago exercise program (OEP).MethodsUsing PubMed, web of science, CNKI, dimensional spectrum, and other databases, search for research papers from 2005 to April 2021 by using keywords such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 51 publications
0
22
0
8
Order By: Relevance
“…The initiative was successful in reaching community-dwelling older adults with low to moderate risk for falls, but not for those at high risk. OEP was chosen by the project team to provide a program for ambulatory older adults that had a high risk of falling ( 27 , 28 ). Challenges with reimbursement from Medicare became an obstacle to implementation of the physical therapist-led version of the program, and concerns over liability and participant safety became an issue for local organizations with the lay-leader, community-based format where sites could only provide limited professional oversight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initiative was successful in reaching community-dwelling older adults with low to moderate risk for falls, but not for those at high risk. OEP was chosen by the project team to provide a program for ambulatory older adults that had a high risk of falling ( 27 , 28 ). Challenges with reimbursement from Medicare became an obstacle to implementation of the physical therapist-led version of the program, and concerns over liability and participant safety became an issue for local organizations with the lay-leader, community-based format where sites could only provide limited professional oversight.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of a series of 17 strength and balance exercises with a walking component. Studies have shown it leads to improved balance, lower leg strength, physical fitness, and self-confidence ( 28 ). It was originally designed to be delivered in the home by a physical therapist (PT), but in the United States this model encountered multiple implementation challenges because of Medicare reimbursement requirements ( 29 , 30 ).…”
Section: Contextmentioning
confidence: 99%
“…Many older adults are able to ac-cess balance and functional exercise classes through communityfunded programs or Silver Sneakers, a fitness program for adults aged 65 years or older that provides access to gyms, community exercise classes, and exercise videos, and is fully covered by most Medicare Advantage and some other insurance plans. 79 A retrospective cohort study in Washington state found an association between intermittent Silver Sneakers use and lower falls risk compared with nonusers (HR, 0.93; 95% CI, 0.90-0.97; absolute benefit not reported). 80 Free online fall exercise programs are available for those in rural areas or those without reliable transportation 81 although effectiveness data are lacking.…”
Section: Practical Considerations and Application Of Evidencementioning
confidence: 99%
“…Durable medical equipment such as canes, walkers, and commode chairs are covered under Medicare Part B for specific diagnoses with a 20% co-pay, and some Medicare Advantage plans also cover additional home safety equipment such as tub chairs and grab bars, although plans vary widely. Many older adults are able to access balance and functional exercise classes through community-funded programs or Silver Sneakers, a fitness program for adults aged 65 years or older that provides access to gyms, community exercise classes, and exercise videos, and is fully covered by most Medicare Advantage and some other insurance plans . A retrospective cohort study in Washington state found an association between intermittent Silver Sneakers use and lower falls risk compared with nonusers (HR, 0.93; 95% CI, 0.90–0.97; absolute benefit not reported) .…”
Section: Practical Considerations and Application Of Evidencementioning
confidence: 99%
“…Eine Metaanalyse zeigte, dass sich durch OEP nicht nur das Sturzrisiko im Folgejahr um ein Drittel reduzierte, sondern auch die Mortalität um 50 Prozent geringer war als in der Kontrollgruppe 68 . Positive Ergebnisse umfassen auch Verbesserungen in der kognitiven Funktion, der Muskelkraft der unteren Extremitäten, der dynamischen und statischen Gleichgewichtsfähigkeit, der Gangstabilität sowie der Fähigkeit zur Haltungskontrolle älterer Menschen 183 . Obwohl Daten bezüglich der Sturzhäufigkeit fehlen, deuten Ergebnisse darauf hin, dass OEP als supervidiertes Gruppentraining bei älteren Menschen mit hohem Sturzrisiko effektiver ist, als OEP-Training allein zu Hause 184 .…”
Section: Vermeidung Des Sturzereignissesunclassified